Prevention of COVID-19-associated Haemostasis Failure in Patient with Stented Coronary Arteries: a Clinical Case - A. V. Samorodov; K. N. Zolotukhin (Креативная хирургия и онкология, 2020)
Introduction. In patients with COVID-19, acute pulmonary lesion grows on inflammation and microvascular thrombosis. Thromboinflammation may develop outside alveolar endothelium and affect endothelium of the heart, kidneys, intestine and other vital organs leading to a multiple-organ insufficiency and possible lethal outcomes. Treatment and prevention of SARS-CoV-2 in the Russian Federation should comply with the Interim Methodological Guidelines of the Russian Ministry of Health that support the global mainstream of COVID-19 containment measures and are updated regularly with new evidence on drug effectiveness, including anticoagulants.Materials and methods. We review a clinical case of effective treatment of a COVID19 patient with prior coronary surgery from the perspective of the Interim Methodical Guidelines of different editions and international clinical experience in anticoagulant therapy.Results and discussion. A retrospective analysis of the patient’s treatment demonstrated the efficacy of thromboelastography in rapid assessment of blood hypercoagulation and parnaparin sodium as a drug of choice among low-molecular heparins in a combined setting with dual antiplatelet therapy. Etiotropic therapy rendered to this patient is currently considered less effective.Conclusion. Combination of anticoagulants with antiaggregants is shown effective under high risks of thrombosis and a background COVID-19 infection, if justified clinically. In cases of complicated diff erential diagnosis, selection of optimal management strategy, anticoagulant and/or antiplatelet therapy monitoring, a good practice is to rely on both the available domestic guidelines and latest meta-analyses combined with international clinical experience.